Optically transparent metasurfaces based on ITO: Numerical design and measurements in THz domain. (17th September 2020) - Shen, Suling; Liu, Qiang; Liu, Xudong; Huang, Jialiang; Jia, Mingyang; Qu, Junle; Shen, Yaochun; Sun, Yiwen
Abstract: Complementary split-ring resonator (CSRR) metasurfaces present interesting applications in terahertz biosensing. Indium tin oxide (ITO) is an essential optoelectronic material because of its optical transparency, high conductivity, and good stability. In this letter, we innovatively suggest that ITO-based CSRR metasurfaces can excite multi-peaks resonance in 0.1–2 THz by numerical simulation and experimental measurements. The multi-peak-resonance presents red-shift characteristics with the increasing external radius of the split-ring. The experimental results are in close agreement with the numerical values, which may indicate that the proposed ITO-based CSRR metasurfaces may play a significant role in visible terahertz biosensing applications.